A Transgressive Figure or a Puppet of the Patriarchy? The Action Heroine in Atomic Blonde - Hilman, Dida Syarifa Nursyamsi; Muktion, Dadung Ibnu (American & British Studies Annual, 2020)
Although women’s empowerment has progressed, various media products still represent women in a negative light. They are commonly stereotyped and shown as sexual objects in these media products. Nonetheless, major breakthroughs have been made in the action film genre. Female action heroes have begun to be represented as transgressive women who oppose the patriarchal notion that masculine qualities are exclusively for men. The film Atomic Blonde features a lead action heroine and presents her as a strong woman who embodies characteristics of both masculinity and femininity. This study aims to discover how this heroine is represented in this action film. A qualitative approach with narrative and non-narrative analysis was applied to conduct this study. In doing so, the writers used Judith Halberstam’s theory of female masculinity that scrutinizes performances of masculinity by female subjects. The theory of gender, sexuality, and toughness by Jeffrey Brown was also employed to examine the aforementioned aspects of action heroines. One research finding is that despite being characterized as a powerful and tough woman, this action heroine is still subjected to hypersexualization and subordination. It demonstrates that regardless of how much power an action heroine possesses, she is still bounded by the patriarchy.